2008
DOI: 10.1186/1471-2105-9-271
|View full text |Cite
|
Sign up to set email alerts
|

TiGER: A database for tissue-specific gene expression and regulation

Abstract: BackgroundUnderstanding how genes are expressed and regulated in different tissues is a fundamental and challenging question. However, most of currently available biological databases do not focus on tissue-specific gene regulation.ResultsThe recent development of computational methods for tissue-specific combinational gene regulation, based on transcription factor binding sites, enables us to perform a large-scale analysis of tissue-specific gene regulation in human tissues. The results are stored in a web da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
315
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(328 citation statements)
references
References 16 publications
9
315
0
4
Order By: Relevance
“…This analysis revealed that a few cell lines, previously thought to be unrelated, were derived from the same patient (Supplementary Data 1). Global mRNA expression profiling was carried out on the entire cell bank and TiGER (tissue-specific gene expression database) 13 was exploited to perform a 'tissue of origin' analysis ( Supplementary Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis revealed that a few cell lines, previously thought to be unrelated, were derived from the same patient (Supplementary Data 1). Global mRNA expression profiling was carried out on the entire cell bank and TiGER (tissue-specific gene expression database) 13 was exploited to perform a 'tissue of origin' analysis ( Supplementary Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty panels of genes with tissue-specific expression were retrieved from the TIGER portal 13 (http://bioinfo.wilmer.jhu.edu/tiger/) and filtered to remove gene symbol redundancies. Similarly, to avoid probe redundancy in array data, when multiple probes matched the same gene we selected the one with the highest s.d.. For the tissue of origin analysis, we assumed that the vast majority of the cell lines present in this data set were of colorectal origin, while only a very small fraction could possibly derive from other tissues.…”
Section: Articlementioning
confidence: 99%
“…We made the same observation even at the whole-genome level, using the National Center for Biotechnology Information reference sequences: CpG-poor promoters were enriched in more hypomethylated DMRs (671 of 16,631) in the centenarian vs. the newborn compared with the annotated CpG island promoters (585 of 23,139) (χ 2 test, P < 3.1 × 10 −16 ). We also analyzed the DMR data with respect to the expression profile of the associated genes obtained from the tissue-specific gene expression and regulation (TiGER) database (27). Considering the expression profile, genes with restricted tissue-specific expression more commonly had DMR hypomethylated sequences in the Y103 sample vs. the NB sample (87%, 56 of 64) than did housekeeping genes (66%, 1,200 of 1,811) (χ 2 test, P < 6.4 × 10 −4 ) (Fig.…”
Section: −16mentioning
confidence: 99%
“…This added APOB SNP (rs1042034) was not in LD with the other identifi ed APOB SNP ( r 2 = 0.094). We next utilized Tissue-Specifi c Gene Expression and Regulation (TIGER) ( 23 ) to examine the tissue expression of these 22 loci to exclude genes not expressed in the stomach, small intestine, or pancreas, with separate confi rmation of nonhepatic gastrointestinal gene expression through the total European Molecular Biology Laboratory (EMBL) Nucleotide Sequence Database ( 24 ). We excluded genes for transcription cholesterol, thereby infl uencing the potential benefi t of lifestyle changes in the prevention of CVD.…”
Section: Snp Selectionmentioning
confidence: 99%